Production of dengue virus-like particles serotype-3 in silkworm larvae and their ability to elicit a humoral immune response in mice - Utomo, Doddy Irawan Setyo (AMB Express, 2020)
To develop monovalent dengue virus-like particle for serotype 3 (DENV-LP/3), we prepared and expressed two structural polyprotein constructs using silkworm and Bm5 cells: DENV-3 Capsid-premembrane-envelope (DENV-3CprME) and premembrane-envelope (DENV-3prME). The expressed PA-tagged 3CprME and 3prME polypeptides were partially purified by PA-tag affinity chromatography and had molecular weights of 85 and 75 kDa, respectively. Expressed proteins were separately verified using the following primary antibodies: the anti-PA tag antibody, DENV premembrane polyclonal antibody, and DENV envelope polyclonal antibody. Transmission electron microscopy revealed that these DENV-3CprME and 3prME formed rough, spherical DENV-LPs (DENV-LP/3CprME and DENV-LP/3prME), respectively, with a diameter of 30–55 nm. The heparin-binding assay demonstrated that these DENV-LPs contained the envelope protein domain III on their surfaces. Both DENV-LPs showed an affinity to sera from human dengue patients and immunized mice. Immunization of mice with DENV-LP/3prME significantly induced the level of antibodies compared with DENV-LP/3CprME. These results indicate that DENV-LP/3prME is suitable as a vaccine candidate compared with DENV-LP/3CprME.